Identification of ZBTB24 protein domains and motifs for heterochromatin localization and transcriptional activation. (15th October 2019) - Aktar, Sharmin; Sasaki, Hiroyuki; Unoki, Motoko
Abstract: Immunodeficiency, centromeric instability, facial anomalies (ICF) syndrome is a rare autosomal recessive disorder caused by mutations in either DNMT3B, ZBTB24, CDCA7, HELLS or an unknown gene(s). Among the known causative genes, ZBTB24 encodes a member of the BTB‐zinc finger (ZF) transcription factor family. The protein possesses a BTB domain, an AT‐hook and eight C2H2 ZF motifs. All ZBTB24 mutations reported in ICF patients are predicted to disrupt at least one ZF motif. Here, we show that both AT‐hook and distinct ZF motifs, particularly the 6th motif, of human and mouse ZBTB24 proteins are important for their heterochromatin localization. On the other hand, the 6th and 7th ZF motifs, and not the AT‐hook or the BTB domain, of the human and mouse proteins are essential for transcriptional activation of CDCA7, another ICF causative gene and a known target of ZBTB24. By deletion analysis of the human CDCA7 promoter, we show that two motifs for ZBTB24 binding are important for transcriptional activation of this gene. These results reveal the evolutionarily conserved domains and motifs important for the biological function of ZBTB24, which provides a basis for understanding the molecular mechanisms underlying the pathogenesis of ICF syndrome. Abstract : ZBTB24 protein, which is composed of a BTB domain, an AT‐hook and eight zinc finger (ZF) motifs, is mutated in ICF syndrome. Our results show that both AT‐hook and distinct ZF motifs, particularly the 6th motif, of the human and mouse proteins, are important for their heterochromatin localization. On the other hand, the 6th and 7th ZF motifs of the human and mouse proteins are essential for transcriptional activation of CDCA7, which is another gene mutated in ICF syndrome.